Integrated power-to-gas and power generation system through chemical looping combustion: a conceptual design. (February 2019) - Ajiwibowo, Muhammad W.; Darmawan, Arif; Huda, Muhammad; Surjosatyo, Adi; Aziz, Muhammad
Abstract: Fossil fuel energy usage will continue to be dominant in the future. Greenhouse emissions will continue to rise unless an alternative way to generate electricity is utilized. Renewable energy sources presents a clean way to produce electricity. However, the intermittency nature of renewable energy sources causes unstable energy production. Energy storage concepts, especially power to gas conversion provides a clean and efficient way to store the overproduced electricity. This paper presents a concept of power to gas energy storage system that is coupled with a chemical looping combustion power generation to provide base load power from the unused electricity in the grid based on a real case of Indonesia. Enhanced process integration is employed in order to achieve an optimal heat and exergy recovery. Preliminary results from simulation using ASPEN Plus V8.8 suggests that a 350 MW power intake for the solid oxide electrolysis system will generate hydrogen that can be utilized for 140 MW power generation with an overall efficiency of 55%. Furthermore, parameters of the system are also evaluated to further improve the system's total efficiency by changing the key design parameters.